Analisis Kinerja SMA Katolik Santo Augustinus dengan Metode Balanced Scorecard - Soputro, Susanty Nenden; Yulia, Yulia; Wibowo, Adi (Jurnal Infra, 2016)
Saint Augustinus Senior High School (SMAK) is a excellent private high school in the Kediri municipality. SMAK currently has 837 students, divided in 24 classes with 40 teachers and 23 employees. This school continues to make progress from year to year with improved governance and activities that support the achievement of the vision and mission of the school. One way to do and made for improved governance is in integrating the data as needed, so that the school can make good decisions and correctly in achieving its vision and mission. By using a balanced scorecard, the school may conduct performance measurement is to help improve the quality of future later. Respondents in this analysis amounts to 80 students and 20 teachers and employees. The method adopted is preparing questionnaires, distributing questionnaires, analyze the results of the questionnaire, and make decisions. Research performance measurement is based on four perspectives of the balanced scorecard.